Analysis on NOX Formation of Biofuels - A. Amiruddin, M.; H. Abdul Rasib, A. (International Journal of Engineering and Technology, 2019)
This paper proposes on analysis of NOX formation of biofuels by using Corn Oil Methyl Ester (COME) and Palm Oil Methyl Ester (POME). The main contribution of this work is to study and analyse NOX emission from biodiesel, which can improve biodiesel content and component in order to reduce NOX formation coming from Compression Ignition (CI) engine. This is achieved by using alkaline base catalyst transesterification process to convert from palm and corn oil, containing low Free Fatty Acid (FFA), to biodiesel or biofuel. Biodiesel ratio, which is 400 ml of cooking oil: 100 ml of methanol: 2.8 g of potassium hydroxide (KOH), is used in transesterification process. The ratio is used to reduce alcohol consumption and cost. Almost 97% of biodiesel are yielded by using this ratio with direct heating from hot magnetic stirrer. The Fourier Transform Infrared Spectroscopy (FTIR) results determine the biodiesels illustrate the exhibition of C=O and C-O, which is the functional groups of esters, whereas the conventional diesel fuel does not have any of the functional groups. In gas emission testing, the biodiesel blends are burned in ceramic beaker including B20, B60 and B100. NOX formation increases when the percentage for biodiesel blends are increase. In ThermaCAM P65 inspection, the testing shows that the temperature is directly proportional with the percentage of biodiesel blends. COME produced the highest amount of NOX than POME and PBDF; POME is the suitable alternative biodiesel fuel that can be used for Compression Ignition engine beside PBDF. The analysis is useful for researchers who intend to reduce NOX emission and improve air cleanliness by determining parameters and factors that can influence NOX formation.Â Â